2005
DOI: 10.1080/10611860500139222
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of choline uptake byN-cyclohexylcholine, a high affinity ligand for the choline transporter at the blood–brain barrier

Abstract: The blood-brain barrier (BBB) choline transporter (CHT) may have utility as a drug delivery vector for drugs that act in the central nervous system. Previous studies suggested the importance of hydrophobic moieties on the cationic nitrogen of choline for improved affinity for this transporter. In a pilot study, we therefore designed five novel N-cycloalkyl derivatives of choline, one of which showed promising inhibition properties. This choline analogue had a cyclohexyl (UMBB-5) moiety substituting one of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…BBB Carrier‐Mediated Transport systems (CMTs) and/or brain delivery vectors, are a feasible option for small molecules to cross the BBB and achieving CNS‐active drug candidates by hitting two targets: a CMT and the corresponding therapeutic target— via prodrug, drug, etc. Nowadays in vivo studies indicate that several compounds may be transported by some CMTs at the BBB 23, 24, 198, 275–288…”
Section: In Silico Models For Blood–brain Barrier Permeability: Predimentioning
confidence: 99%
See 1 more Smart Citation
“…BBB Carrier‐Mediated Transport systems (CMTs) and/or brain delivery vectors, are a feasible option for small molecules to cross the BBB and achieving CNS‐active drug candidates by hitting two targets: a CMT and the corresponding therapeutic target— via prodrug, drug, etc. Nowadays in vivo studies indicate that several compounds may be transported by some CMTs at the BBB 23, 24, 198, 275–288…”
Section: In Silico Models For Blood–brain Barrier Permeability: Predimentioning
confidence: 99%
“…Over 98% of small molecules intended for therapeutic use in the CNS never reach the market because of their inherent inability to cross the BBB 21, 22. The BBB effectively restricts delivery of valuable pharmaceuticals to the brain thereby presenting major therapeutic limitations toward the treatment of CNS diseases 23, 24. It is reported that 12% of all drugs are active in the CNS, but only 1% of all drugs are active in the brain for diseases other than affective disorders 25.…”
Section: Introductionmentioning
confidence: 99%
“…Choline transport is characterized by sodiumdependent high-affinity, sodium-independent low-affinity, and sodium-independent bloodbrain barrier transport mechanisms (Crowe et al, 2002;Lockman and Allen, 2002). The choline transporters of the blood brain barrier are inhibited by close structural analogs of choline and quaternary amines (Ferguson and Collier, 1994;Geldenhuys et al, 2005;Cai et al, 2007). Changes in the activity of these transporters induced by close analogues of choline has direct impact on levels of brain acetylcholine (Sterling et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Rats or mice administered [ 14 C]DMAE via intracerebral injection were observed with rapid clearance of DMAE and increases in brain levels of phosphatidylethanolamine, phosphotidylethanolamine, or other acid-soluble and lipid cholines (Schlenk, 1990). In female mice administered 0.1 mg/kg [1,[2][3][4][5][6][7][8][9][10][11][12][13][14]…”
Section: Introductionmentioning
confidence: 99%